Micro and smart devices and systems - Vinoy, K. J. [ed.]; Ananthasuresh, G. K. [ed.]; Pratap, Rudra [ed.]; Krupanidhi, S. B. [ed.] (New Delhi Springer, 2014)
The book presents cutting-edge research in the emerging fields of micro, nano and smart devices and systems from experts working in these fields over the last decade. Most of the contributors have built devices or systems or developed processes or algorithms in these areas. The book is a unique collection of chapters from different areas with a common theme and is immensely useful to academic researchers and practitioners in the industry who work in this field.
Keywords: Nanotechnology; Smart materials; Microtechnology